Facile Synthesis of Novel Nanostructured MnO2Thin Films and Their Application in Supercapacitors - Xia H; Xiao W; Lai MO; Lu L (Nanoscale Research Letters, 2009)
Abstract Nanostructured α-MnO2thin films with different morphologies are grown on the platinum substrates by a facile solution method without any assistance of template or surfactant. Microstructural characterization reveals that morphology evolution from dandelion-like spheres to nanoflakes of the as-grown MnO2is controlled by synthesis temperature. The capacitive behavior of the MnO2thin films with different morphologies are studied by cyclic voltammetry. The α-MnO2thin films composed of dandelion-like spheres exhibit high specific capacitance, good rate capability, and excellent long-term cycling stability.